Resistance profiling of Aspergillus fumigatus to olorofim indicates absence of intrinsic resistance and unveils the molecular mechanisms of acquired olorofim resistance. Issue 1 (31st December 2022) - Buil, Jochem B.; Oliver, Jason D.; Law, Derek; Baltussen, Tim; Zoll, Jan; Hokken, Margriet W. J.; Tehupeiory-Kooreman, Marlou; Melchers, Willem J. G.; Birch, Mike; Verweij, Paul E.
ABSTRACT: Olorofim (F901318) is a new antifungal currently under clinical development that shows both in vitro and in vivo activity against a number of filamentous fungi including Aspergillus fumigatus . In this study, we screened A. fumigatus isolates for intrinsic olorofim-resistant A. fumigatus and evaluated the ability of A. fumigatus to acquire an olorofim-resistant phenotype. No intrinsic resistance was found in 975 clinical A. fumigatus isolates. However, we found that isolates with increased olorofim MICs (> 8 mg/L) could be selected using a high number of conidia and olorofim exposure under laboratory conditions. Assessment of the frequency of acquired olorofim resistance development of A. fumigatus was shown to be higher than for voriconazole but lower than for itraconazole. Sequencing the PyrE gene of isogenic isolates with olorofim MICs of >8 mg/L identified various amino acid substitutions with a hotspot at locus G119. Olorofim was shown to have reduced affinity to mutated target protein dihydroorotate dehydrogenase (DHODH) and the effect of these mutations was proven by introducing the mutations directly in A. fumigatus . We then investigated whether G119 mutations were associated with a fitness cost in A. fumigatus. These experiments showed a small but significant reduction in growth rate for strains with a G119V substitution, while strains with a G119C substitution did not exhibit a reduction in growth rate. These in vitro findings were confirmed in an in vivo pathogenicity model.